Prevalence and Determinants of Wheezing and Bronchodilatation in Children With Cystic Fibrosis: A Retrospective Cohort Study - Francois Galodé; O. Ladipo; A. Andrieux; H. Feghali; S. Bui; Michael Fayon; Michael Fayon (Frontiers Media S.A., 2022)
BackgroundMany patients with cystic fibrosis (CF) wheeze, and are dubbed as having CF-asthma. Understanding the determinants of such wheezing may avoid unnecessary treatments and open newer treatment avenues.ObjectivesMain: To evaluate the prevalence and characteristics of wheezing and a positive bronchodilatory response (BDR) in children with CF. Secondary: To identify the predictive markers and the impact of current wheezing a positive BDR.MethodsA retrospective single-center study in children with CF. We determined the characteristics of physician-reported wheeze in patients <6 years, and a BDR in patients aged 6-17 years. Anthropometric, lung function, laboratory, genetic and microbiological data were recorded in all groups. Variables were compared using the Chi2 and Student t-tests, and ANOVA.Results125 preschool and 69 school-aged children and adolescents with CF were included in the study. 71.2% of patients <6 years of age had had at least one episode of wheezing: 26.3% of patients were Transient Early Wheezers, 12.6% Late Onset Wheezers and 37.9% were Persistent Wheezers. The prevalence of a positive BDR was 73.5, 48.5, and 52.9% in the 6-8 years, 10-12 years, and 15-17 years age groups, respectively. Allergic factors were not predictive of wheezing in preschoolers. In the 6-8 years age group, the sum of wheal diameters of allergic skin prick tests (SPT, house dust mite + cat + dog dander) was greater in those with a BDR vs. no BDR (4 [2.0-8.8] vs. 1 [0-7.0] mm, p = 0.01). The presence of Pseudomonas aeruginosa in the bronchial secretions before 3 years of age was not significantly associated with either the presence of wheezing at the age of 6 years or a BDR in school-aged children and adolescents. The proportion of homozygous p.F508del patients was significantly lower in the group of patients who had wheezed by 6 years of age (60% vs. 72.7%, p = 0.009), but higher in the 6-8 years old group with a BDR vs. no BDR (64% vs. 36%, p = 0.04). Current wheezers at 6 years had a lower mean FEV1 vs. the non-current wheezers (91.5 ± 4.4% vs. 100.9 ± 2.4%; p = 0.047). Similarly, forced vital capacity (FVC) was significantly lower in the 6-8 years old group with BDR vs. no BDR (85 ± 19 vs. 101 ± 21%, p = 0.015).ConclusionWheezing and BDR are very frequent findings in children with CF. Current wheeze at the age of 6 years was associated with worse lung function. Labeling wheezing in CF as "CF-Asthma" is misleading since the determinants are different, and may lead to inappropriate prescriptions of inhaled steroids.